Measurement of neural respiratory drive via parasternal intercostal electromyography in healthy adult subjects. (25th October 2016) - MacBean, V; Hughes, C; Nicol, G; Reilly, C C; Rafferty, G F
Abstract: Neural respiratory drive, quantified by the parasternal intercostal muscle electromyogram (EMGpara), provides a sensitive measure of respiratory system load-capacity balance. Reference values for EMGpara-based measures are lacking and the influence of individual anthropometric characteristics is not known. EMGpara is conventionally expressed as a percentage of that obtained during a maximal inspiratory effort (EMGpara%max), leading to difficulty in applying the technique in subjects unable to reliably perform such manoeuvres. To measure EMGpara in a large, unselected cohort of healthy adult subjects in order to evaluate relevant technical and anthropometric factors. Surface second intercostal space EMGpara was measured during resting breathing and maximal inspiratory efforts in 63 healthy adult subjects, median (IQR) age 31.0 (25.0–47.0) years, 28 males. Detailed anthropometry, spirometry and respiratory muscle strength were also recorded. Median (IQR EMGpara was 4.95 (3.35–6.93) µ V, EMGpara%max 4.95 (3.39–8.65)% and neural respiratory drive index (NRDI, the product of EMGpara%max and respiratory rate) was 73.62 (46.41–143.92) %.breath/min. EMGpara increased significantly to 6.28 (4.26–9.93) µ V ( p < 0.001) with a mouthpiece, noseclip and pneumotachograph in situ . Median (IQR) EMGpara was higher in female subjects (5.79 (4.42–7.98) µ V versus 3.56 (2.81–5.35) µ V, p = 0.003); after controlling for sex neither EMGpara, EMGpara%max or NRDI were significantly related to anthropometrics, age or respiratory muscle strength. In subjects undergoing repeat measurements within the same testing session ( n = 48) or on a separate occasion ( n = 19) similar repeatability was observed for both EMGpara and EMGpara%max. EMGpara is higher in female subjects than males, without influence of other anthropometric characteristics. Reference values are provided for EMGpara-derived measures. Expressing EMGpara as a percentage of maximum confers no advantage with respect to measurement repeatability, expanding the potential application of the technique. Raw EMGpara is a useful marker of respiratory system load-capacity balance.